CONDUCTING BREEDING, SEED PRODUCTION WORK ON FORAGE CROPS RESISTANT TO SALINITY AND WATER SCARCITY IN THE ARAL SEA AREA’S (Multidisciplinary Journal of Science and Technology, 2026)
One of the biggest problems of the world community today is the Aral Sea problem. It is noted that over the past 80 years, the Aral Sea has lost more than 1 billion tons of water. By the 2000s, the sea had almost completely disappeared: the water level dropped, salinity increased, and the ecosystem was disrupted. The disappearance of the sea caused droughts, dust storms, and extreme temperatures. The air was filled with dust, salts, and pesticides, leading to an increase in a number of diseases. The lands became unsuitable for agriculture. In order to partially eliminate this problem, the sowing and testing of fodder crops on the dried seabed of the island and the development of technologies for growing these crops, taking into account the soil and climatic conditions of the region, the establishment of primary seed production of varieties suitable for the region, and the supply of seeds based on demand are urgent tasks today.This article presents data obtained as a result of work carried out in experimental nurseries where local and foreign varieties and samples of fodder crops were planted to select crop types, varieties and samples suitable for local soil and climatic conditions on the dried bottom of the island and in the Aral Sea area’s.